Comparative Evidence for Intrahepatic Cholestasis of Pregnancy Treatment With Traditional Chinese Medicine Therapy: A Network Meta-Analysis - Jiang, Yinxiao; Li, Haotian; Song, Dan; Ye, Penghui; Xu, Nuo; Chen, Yuan; Zhang, Wenwen; Hu, Qichao; Ma, Xiao; Wen, Jianxia; Li, Yeyu; Zhao, Yanling (Frontiers in Pharmacology, 2021)
Background: Intrahepatic cholestasis of pregnancy (ICP) seriously threatened the health of pregnant women and newborns. The number of Chinese prescriptions and patent medicines are used to treat ICP combined with UDCA in China. However, the choice of treatment remains questionable. Methods: PubMed, Embase, Cochrane library and four Chinese databases including CNKI, CBM, Wanfang database and VIP database were comprehensively searched. Intrahepatic cholestasis of pregnancy was disease keywords. The Intervention plans included single using UDCA, Chinese prescriptions combine with UDCA and patent medicine combine with UDCA. We searched related RCTs from database inception to February 22, 2021. Pre-prepared forms were used to collect the data. In addition, different patent medicine was divided into different groups. Chinese prescriptions were divided 5 groups based on Yinchenhao Decoction. Further, the reasonable model was chosen to do network meta-analysis. The main outcomes included pruritus score and the level of TBA, ALT, AST. This study is registered with PROSPERO, and the number is CRD42020188831. Results: 38 RCTs (3841 patients) were included in the network meta-analysis. The results indicated that IP-f [the similar prescription of Yinchenhao decoction 2 (Artemisia capillaris Thunb > 15 g, Gardenia > 9 g, Rhubarb < 5 g) + UDCA] was the best therapeutics among 8 therapies. Furthermore, in the outcome of pruritus score, the therapeutic effect of IP-a was significantly lower than the IP-f and IP-g. In the outcome of TBA, the therapeutic effect of IP-a was significantly lower than the IP-f, IP-g, IP-b, IP-h, IP-d. In the outcome of ALT, the therapeutic effect of IP-a was significantly lower than the IP-e, IP-f and IP-b. In the outcome of AST, the therapeutic effect of IP-a was lower than the IP-b and IP-f. Conclusions: The therapies that Chinese prescriptions or patent medicine combine with UDCA were generally better than UDCA alone. Only an accident, IP-a was better than IP-d in terms of improving the level of ALT. The proportion of medicine used is different from the traditional proportion of Yinchenhao Decoction. Therefore, the dose of IP-f could provide a huge reference for the clinical medication.